Engineering calculations in radiative heat transfer - Gray, W. A. (William Alan); Muller, Rudolph (International series on materials science and technology, 1974)
Engineering Calculations in Radiative Heat Transfer is a six-chapter book that first explains the basic principles of thermal radiation and direct radiative transfer. Total exchange of radiation within an enclosure containing an absorbing or non-absorbing medium is then described. Subsequent chapters detail the radiative heat transfer applications and measurement of radiation and temperature.